Principal’s Management Competencies in Improving the Quality of Education - Komalasari, Komalasari; Arafat, Yasir; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2020)
This study determined the management competence of principals in improving the quality of education in SD Negeri 1 Epil, Lais District, Musi Banyuasin Regency. This research method is a qualitative descriptive. Sources of data in this study were teachers who assisted in the learning process at SD Negeri 1 Epil, Lais District, Musi Banyuasin Regency. Data collection techniques in this study include 1) interviews and 2) documentation. The data analysis used in this study were 1) data reduction, 2) display or presentation of data and 3) conclusions and data verification. The results showed that the management competence of the principal in improving the quality of education in Lais District was good. This paper contributes to upgrade the principal’s management competence in order to improve the quality of education.